Students’ Word Pronunciation Errors in Reading Aloud English Paragraph - Pratiwi, Nanda Rian; Affini, Laily Nur; Musarokah, Siti (Universitas Pahlawan Tuanku Tambusai, 2024)
This research analyzes the errors in students' pronunciation when students read a paragraph aloud. Data was obtained from research on 15 class XI students of SMK Swadaya Semarang. They were taken using a simple random sampling method. The data collection technique is that students record their voices while reading, which the researcher then transcribes the recording into phonetics to analyze errors. The results of the research show that most students replace sounds that are not found in Indonesian and replacing English vowels with Indonesian vowels. Students are familiar with the following phoneme similarities: /i/ as /i:/, /i/ and /e/ as /ae/ , /ʌ/ as /ɑː/, /ə/ as /ɜː/, /ɒ / as / ɔː/, /e/ as /æ/, and /u/ as /ʊ/, /u:/. Thus, it seems that there are still many students who still have difficulty pronouncing English words correctly because their tongues are not yet used to vowels other than the vowels in their mother tongue.